(untitled) (Journal of Environmental Science and Natural Resources, 2016)
An experiment was conducted to compare the performance between traditional farming and organic farming of freshwater prawn in respect of production and economics. The experiment had two treatments, namely: Traditional (TT) and Organic (TO) with same stocking density (20000 juveniles ha-1) in triplicate. In treatment TO, formulated feed with locally available ingredients were used, and maize flour and bamboo branches were provided for maintaining C:N ratio to 20 and for developing periphyton, respectively. In treatment TT, only commercially available prawn feed was applied. No fertilizers or other types of chemicals or antibiotics were used in both treatments. There were no significant differences (P?0.05) of different water quality parameters between both treatments. Weight gain and specific growth rate (% body weight day-1) of prawn was significantly higher (P<0.05) in TO than TT treatment. Survival rate and feed conversion ratio of prawn did not vary significantly between both treatments. Highest total yield was obtained from TO treatment (511.41 kg ha-1 90 d-1) compared to TT treatment (426.57 kg ha-1 90 d-1). Net yield was also significantly higher in treatment TO (428.32 kg ha-1 90 d-1) than TT (347.77 kg ha-1 90-1). Although there was no significant difference in benefit-cost ratio between both treatments, totalreturn was significantly higher in TO than TT treatment. J. Environ. Sci. & Natural Resources, 9(1): 109-116 2016